Teledentistry: The Need of An Hour During Pandemic COVID-19 - Jyoti Prajapat, S; Rajesh Prajapat; Sowmya H K; Sanjeev B Khanagar; Prabhadevi C Maganur; Satish Vishwanathaiah (Institute of Medico-legal Publications Pvt Ltd, 2021)
The epidemic of coronavirus disease 2019 (COVID-19), originating in Wuhan, China, has become a majorpublic health challenge. According to WHO, “It is possible to halt the virus spread, by adopting measuresto detect disease early, isolate and treat the cases, tracing the people who came in contact with those whoare infected, wearing gloves and masks, limitation of people going outside their home and promote socialdistancing measures.” Due to the characteristics of dental settings, the risk of cross infection can be highbetween patients and dental practitioners and can spread from patient to patient.As part of its efforts tomitigate the spread of the COVID-19 pandemicthe American Dental Association (ADA) provided essentialguidance on (i) emergency vs. nonemergency dental care and (ii) the use of teledentistry. In response to thecurrent health crisis, teledentistry is emerging as a viable care option in an effort to help “flatten the curve”of the COVID-19 pandemic.During the COVID-19 outbreak, teledentistry is an effective way to triagepatients and conduct problem-focused evaluations in order to limit office visits to patients needing urgent oremergency care. This article, based on relevant guidelines and research, introduces the essential knowledgeabout COVID-19, and focuses on how teledentistry can be helpful in preventing dental emergencies byproviding effective dental care to patients during quarantine, and also educate and motivate people to optnecessary dental hygiene measures.